Redefining meta-competencies, competencies, and skills of digital journalists - López-García, Xosé (Anuario ThinkEPI, 2022)
The digital transition has led journalism and journalists into the scenario that shapes today´s communication ecosystem and that demands new competencies and skills to exercise the profession. In three decades of changes, we have gone from the first digital migration, the emergence of digital-native media, the arrival of blogs, the rise of mobile communication, the emergence of social media networks, the rise of the social web, the application of virtual reality to certain pieces, the emergence of artificial intelligence, etc. to the rise of 5G and blockchain technologies. This transition has meant leaving behind a one-to-many communication model to bring many-to-many communication to the forefront, placing us in a liquid and platformized society. Communication is in the environment, being ubiquitous, while disinformation accompanies us in every movement and the challenges of building better-informed societies are multiplying. Journalists need up-to-date competencies and skills if they want to inform about what is happening in this complex networked society. Curricula are trying to respond to this challenge, while reflections on the best formulas combining sociocultural and sociotechnological competencies and skills are multiplying. After this phase of experimentation, this challenge calls for a renewal of proposals for the second half of the third decade of the millennium.